2021
DOI: 10.3390/molecules26133821
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Scaffolds for the Dual Inhibition of HIV-1 RT Polymerase and Ribonuclease Associated Functions

Abstract: Current therapeutic protocols for the treatment of HIV infection consist of the combination of diverse anti-retroviral drugs in order to reduce the selection of resistant mutants and to allow for the use of lower doses of each single agent to reduce toxicity. However, avoiding drugs interactions and patient compliance are issues not fully accomplished so far. Pursuing on our investigation on potential anti HIV multi-target agents we have designed and synthesized a small library of biphenylhydrazo 4-arylthiazol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Escherichia coli strain M15 containing the p6HRT-prot vector (provided by Stuart Le Grice laboratory (NCI Frederick)) was grown to an optical density at 600 nm of 0.7 and induced with 1.7 mM of isopropyl b-D-1-thiogalactopyranoside (IPTG) for 4 h. (A) Previously reported allosteric HIV RT dual inhibitors (Distinto et al, 2012;Meleddu et al, 2014;Meleddu et al, 2015;Corona et al, 2016a;Meleddu et al, 2017;Meleddu et al, 2021). Ar, aromatic substituents.…”
Section: Expression and Purification Of Recombinant Hiv-1 Rt Hiv-1 Rt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Escherichia coli strain M15 containing the p6HRT-prot vector (provided by Stuart Le Grice laboratory (NCI Frederick)) was grown to an optical density at 600 nm of 0.7 and induced with 1.7 mM of isopropyl b-D-1-thiogalactopyranoside (IPTG) for 4 h. (A) Previously reported allosteric HIV RT dual inhibitors (Distinto et al, 2012;Meleddu et al, 2014;Meleddu et al, 2015;Corona et al, 2016a;Meleddu et al, 2017;Meleddu et al, 2021). Ar, aromatic substituents.…”
Section: Expression and Purification Of Recombinant Hiv-1 Rt Hiv-1 Rt...mentioning
confidence: 99%
“…Although some reports suggested that RNase H inhibitors could negatively impact the activity of NRTIs such as AZT (Davis et al, 2011), it is worthy of note that some RNase H inhibitors were also reported to retain full potency of inhibition against HIV-1 vectors that carry well-known INSTI, NNRTI, and NRTI resistance mutations in a single round of replication (Boyer et al, 2018) and have full potency against HIV-1 K103N-Y181C replicant virus conferring cytoprotective effect in a 5 days of cytopathic effect (CPE) assay (Corona et al, 2020), making them very appealing as potential therapeutics to treat the circulating drug-resistant strains. Allosteric inhibition of RNase H/RDDP has been described for scaffolds characterized by variously substituted aromatic portions linked by a functionalized spacer containing groups capable of donating or accepting hydrogen bonds, whether linear or made from heterocyclic rings (Distinto et al, 2013;Meleddu et al, 2014;Meleddu et al, 2015;Meleddu et al, 2017;Sonar et al, 2017;Esposito et al, 2019;Fois et al, 2021;Meleddu et al, 2021). It has been proposed that these compounds possess an innovative mechanism of action since they could bind two different allosteric RT pockets: the first one is located at the DNA polymerase domain (partially overlapping the NNRTI binding pocket), and the second one is under the active RNase site H near the interface between p66/p51 (Corona et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting dual antiviral inhibitor was developed from acyclic nucleotide phosphonate derivatives, such as adefovir (11) and tenofovir (12), for the treatment of HIV and hepatitis B virus co-infection [67]. The MTDL strategy can also be applied to combine hitherto unexplored or less explored anti-HIV activities in a single molecule by starting from a suitable lead [68]. These examples also immediately highlight one of the important advantages of DML/MTDL over combination formulations that pharmacokinetics and pharmacodynamics can be optimized, although undoubtedly, chemical lead optimization requires the synthesis of many compounds and a very thorough and detailed series of pharmacological experiments, including phenotypebased assays to evaluate the balanced profile, pharmacokinetic, and safety studies.…”
Section: Dual Ccr5 and Cxcr4 Antagonistsmentioning
confidence: 99%